Live Birth With or Without Preimplantation Genetic Testing for Aneuploidy. Issue 3 (March 2022) - Yan, Junhao; Qin, Yingying; Zhao, Han; Sun, Yun; Gong, Fei; Li, Rong; Sun, Xiaoxi; Ling, Xiufeng; Li, Hong; Hao, Cuifang; Tan, Jichun; Yang, Jing; et al.
Abstract : (Abstracted from N Engl J Med 2021;385:2047–2058) To optimize live birth rate per transfer in in vitro fertilization (IVF), morphologic score based on visualization and genetic status based on preimplantation genetic testing for aneuploidy (PGT-A) are used to select the highest quality embryos. Although some studies suggest an increased live birth rate among women of advanced maternal age, it is less clear whether PGT-A in women with good prognosis for live birth experience a similar benefit.